ISLAM AND PLURALITY OF SOCIETY IN WEST KALIMANTAN - Zulkifli Abdillah (Al-Albab, 2012)
The plurality of the society in West Kalimantan has been formed since the earliest days of the appearance of Islamic style kingdoms or sultanates. However, in its development in the last few decades, the plurality has created social conflicts, especially among Muslims themselves. By using the perspective of normative teachings of Islam and the historicity of its congregants, this paper aims to present the argument that plurality is a thing that must be accepted by anyone as an inevitability. Keywords: Plurality of society, Malay, Dayak.